English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-01-20 04:47:49 · 22 answers · asked by Lucia O 1 in Science & Mathematics Mathematics

22 answers

Working on how you have written it

(4x3) - (12x2) = 9x - 27

12 -24 = 9x - 27

-12 = 9x - 27

15 = 9x

x = 15/9

x = 5/3

x = 1 2/3

Of course you could mean 4x^3 - 12x^2 = 9x - 27, but that's not what you have written

2007-01-20 04:52:05 · answer #1 · answered by Anonymous · 2 1

x=3

2007-01-25 05:01:32 · answer #2 · answered by black 1 · 0 0

ok I'm assumming that the numbers after the x are exponants so that is how I'm going to solve this.
4x^3-12x^2=9x-27
first set equal to zero by subtracting 9x-27 from both sides
4x^3-12x^2-9x+27=0
you now have to use the difference of cubes formula
4x^2(x - 3) - 9(x -3) = 0
(x - 3)(4x^2 - 9) = 0
(x - 3)[(2x)^2 - (3)^2] = 0 < (x - 3)(2x - 3)(2x + 3) = 0
solve for x
(x-3)=0 x=3
2x-3=0 x=3/2
2x+3=0 x=-3/2
x = 3, 3/2, -3/2
check your answers in the original problem to make sure they work and you don't get anything goofy like an imaginary number

2007-01-20 04:56:35 · answer #3 · answered by Doug H 3 · 1 0

12=18

2007-01-28 02:56:37 · answer #4 · answered by shay 2 · 0 0

Do you mean: 4x^3 - 12x^2 = 9x - 27
Or, (4)(3) - (12)(2) = 9x - 27? It could be written either way, depending on what your book has. I'll solve both equations...

1. 4x^3 - 12x^2 = 9x - 27
First: set the equation to equal "0" ...subtract "9x" from both sides...

4x^3 - 12x^2 - 9x = 9x - 9x - 27
4x^3 - 12x^2 - 9x = - 27

*Add "27" to both sides...

4x^3 - 12x^2 - 9x + 27 = - 27 + 27
4x^3 - 12x^2 - 9x + 27 = 0

Sec: when you have 4 terms - group "like" terms & factor...

(4x^3 - 12x^2) - (9x + 27) = 0
4x^2(x - 3) - 9(x - 3) = 0
(x - 3)(4x^2 - 9) = 0

*Factor "4x^2 - 9" > its the difference of squares...

(x - 3)(2x + 3)(2x - 3) = 0

Third: you have three x-variables to solve for > set each term to equal "0"

a) x - 3 = 0
x - 3 + 3 = 0 + 3
x = 3

b) 2x + 3 = 0
2x + 3 - 3 = 0 - 3
2x = - 3
2x/2 = - 3/2
x = -3/2

c) 2x - 3 = 0
2x - 3 + 3 = 0 + 3
2x = 3
2x/2 = 3/2
x = 3/2

2. Solve for "x" > (4)(3) - (12)(2) = 9x - 27

First: use order of operations - PEMDAS > ( ), exponents, multiplication, division, addition & subtraction

12 - 24 = 9x - 27

- 12 = 9x - 27

Sec: add "27" to both sides...

- 12 + 27 = 9x - 27 + 27
15 = 9x

Third: solve for "x" by isolating it on one side > divide both sides by "9"

15/9 = 9x/9
15/9 = x
x = 15/9

*Simplify the fraction into lowest terms, if possible..

x = 5/3

2007-01-20 05:02:59 · answer #5 · answered by ♪♥Annie♥♪ 6 · 0 1

x=3

2007-01-20 04:52:02 · answer #6 · answered by MsAdventure 5 · 0 2

As understood>>
4x^3 - 12x^2 = 9x - 27
Transferring all to left side
4x^3 - 12x^2 - 9x + 27 = 0
4x^2(x - 3) - 9(x -3) = 0
(x - 3)(4x^2 - 9) = 0
(x - 3)[(2x)^2 - (3)^2] = 0 <>
(x - 3)(2x - 3)(2x + 3) = 0
Solving for x
x = 3, 3/2, -3/2

2007-01-20 04:57:05 · answer #7 · answered by Sheen 4 · 2 0

you need () to show sequence of operation
(4x3)-(12x2)=9x-27
12-24+27=9x
15=9x
x=15/9
x=5/3 or 1.6666666

2007-01-20 05:00:42 · answer #8 · answered by verner66 2 · 0 2

4x3 - 12x2 = 9x - 27
12 - 24 = 9x - 27
-12 = 9x - 27
-12 + 27 = 9x -27 + 27
15 = 9x
15/9 = 9x/9
1 2/3 = x

2007-01-20 04:56:14 · answer #9 · answered by Dex 1 · 0 2

you write 4x3-12x2=9x-27
so first part is easy as in 4x3=12-12=0x2=0
second part just as easy as 9x?- 27 so ? is 3 as in 9x3-27=0
you wrote it down fine . nothing wrong with what you did
as you want x =3

2007-01-20 05:14:57 · answer #10 · answered by noblueloo 2 · 0 1

fedest.com, questions and answers